Kekerasan dalam media Massa dan Makna Pers Pancasila - Soemadi M Wonohito (Unisia, 2006)
The following article tries to explain the violence that publishes either in printed media or in electronic media. Mass media is often criticized when publish or display violence news although fact-based. The violence of media implies trauma. Trauma is not only individual psychological aspect, but also social structure, political authority, and the cultural values. In this sense trauma can not only handled and solved by psychologists but also should need anthropologists, sociologists and other fields of social scientists participation to identify the factors the above mentioned.